Review of infectious agent occurrence in wild salmonids in British Columbia, Canada. Issue 2 (19th November 2019) - Jia, Beibei; Delphino, Marina K. V. C.; Awosile, Babafela; Hewison, Tim; Whittaker, Patrick; Morrison, Diane; Kamaitis, Mykolas; Siah, Ahmed; Milligan, Barry; Johnson, Stewart C.; Gardner, Ian A.
Abstract: Wild Pacific salmonids (WPS) are economically and culturally important to the Pacific North region. Most recently, some populations of WPS have been in decline. Of hypothesized factors contributing to the decline, infectious agents have been postulated to increase the risk of mortality in Pacific salmon. We present a literature review of both published journal and unpublished data to describe the distribution of infectious agents reported in wild Pacific salmonid populations in British Columbia (BC), Canada. We targeted 10 infectious agents, considered to potentially cause severe economic losses in Atlantic salmon or be of conservation concern for wild salmon in BC. The findings indicated a low frequency of infectious hematopoietic necrosis virus, piscine orthoreovirus, viral haemorrhagic septicaemia virus, Aeromonas salmonicida, Renibacterium salmoninarum, Piscirickettsia salmonis and other Rickettsia‐like organisms, Yersinia ruckeri, Tenacibaculum maritimum and Moritella viscosa . No positive results were reported for infestations with Paramoeba perurans in peer‐reviewed papers and the DFO Fish Pathology Program database. This review synthesizes existing information, as well as gaps therein, that can support the design and implementation of a long‐term surveillance programme of infectious agents in wild salmonids in BC.